Implementation of Project-Based Learning in Increasing Students Writing Skills at IISIP YAPIS Biak Papua - Jelita Purnamasari (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2024)
This research was aimed to find out whether the implementation of Project Based Learning can be effectively increasing students’ writing skills. Quantitative method was used in this research by giving pre-test and post-test in order to know the students’ productivity in writing. There were 25 students as the participants. They were in the fifth semester in which 13 students became the experimental class and the 12 students became the controlled class. The mean score showed that the pretest was 50 and the score of the posttest was 76,15. The percentage and frequency of the students’ score on the pretest for experimental class showed that 7 or 54% got an average score, 5 or 38% got a poor score, and 1 or 8% got a very poor score. While, after the researcher conducted the project based learning, the posttest showed that 5 or 38% of students got very good scores, 2 or 15% of students got a good score and 6 or 46% students got an average score. There was a significant difference between the pretest and posttest. based on the result, there was a significant difference between the experimental class and the controlled class in their writing achievement. Hence, the implementation of project based learning was effective in increasing students' writing ability in writing news.